2014
DOI: 10.7852/ijie.2014.29.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rearing season, host plants and their interaction on economical traits of tropical tasar silkworm, Antheraea mylitta Drury- an overview

Abstract: Tropical tasar silkworm, Antheraea mylitta (Lepidoptera: Saturniidae) is a polyphagous silk producing forest silkworm of commercial importance in India. Forest dependent people rear its larvae on different forestry host plants twice or thrice in a year for small household income. Larvae of A. mylitta feeds on many forest tree species, but always show a great degree of selectivity as a function of its behavioural responses to physical structure and chemical features of the host plants. Cocoon crop of A. mylitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 81 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…The quality and quantity of tasar host plants is directly correlated to its environment, even micro climate change influence the soil micro flora thereby affecting the mobilization of minerals. The nutritional quality of leaf influences the feeding behavior, growth and finally development of silkworm which later affect the cocoon quality and dfl production (Bhatia andYousuf, 2014 andRam et al, 2016). Prolonged rearing duration due to low nutritive value of foliage has serious implications like predatory pressure, population segregation and occurrence of pests and diseases (Bora andSaikia, 2022 andLokesh et al, 2016).…”
Section: Challenges Of Climate Changementioning
confidence: 99%
“…The quality and quantity of tasar host plants is directly correlated to its environment, even micro climate change influence the soil micro flora thereby affecting the mobilization of minerals. The nutritional quality of leaf influences the feeding behavior, growth and finally development of silkworm which later affect the cocoon quality and dfl production (Bhatia andYousuf, 2014 andRam et al, 2016). Prolonged rearing duration due to low nutritive value of foliage has serious implications like predatory pressure, population segregation and occurrence of pests and diseases (Bora andSaikia, 2022 andLokesh et al, 2016).…”
Section: Challenges Of Climate Changementioning
confidence: 99%
“…RGD is present in the protein sequence of silk fibroins produced by Antheraea mylitta; 28 however, Antheraea mylitta is difficult to rear in a laboratory setting with detrimental impacts on silk production with current indoor rearing protocols. 29 Antheraea mylitta has seasonally dependent life cycles that are around 2 months long, where production is impacted by external factors (e.g., climate change 30 ). Current collection methods for Antheraea mylitta include rearing in a forest with human-based collection from the forest, 30,31 meaning that production is outdoors, eliminating a researcher's or company's control over rearing conditions prior to use in manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Antheraea mylitta has seasonally dependent life cycles that are around 2 months long, where production is impacted by external factors (e.g., climate change). Current collection methods for Antheraea mylitta include rearing in a forest with human-based collection from the forest, , meaning that production is outdoors, eliminating a researcher’s or company’s control over rearing conditions prior to use in manufacturing. This is a common challenge for translating alternative silk-producing species to biomedical applications, and while Plodia ’s fibroin proteins do not contain RGD, its standardized indoor rearing parameters warrant further investigation on how its unique sequence in the silk biomaterial space can be leveraged.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant for tropical Tasar sericulture. Bhatia and Yousuf (2014) and Jena (2016) demonstrated that seasonal availability of diet with balanced levels of nutrients is an important prerequisite for rearing this insect.…”
Section: Introductionmentioning
confidence: 99%